Association Between Adherence to Healthy Lifestyles and Depressive Symptoms Among Japanese Hospital Workers During the COVID-19 Pandemic. (November 2021) - Fukunaga, Ami; Inoue, Yosuke; Yamamoto, Shohei; Miki, Takako; Nanri, Akiko; Ishiwari, Hironori; Ishii, Masamichi; Miyo, Kengo; Konishi, Maki; Ohmagari, Norio; Mizoue, Tetsuya
The objective of this study was to investigate the association between adherence to healthy lifestyles (as measured by the healthy lifestyle index [HLI]) and depressive symptoms among staff members at a large national medical institution in Tokyo, Japan, during the coronavirus disease 2019 (COVID-19) pandemic. The study sample consisted of 1228 staff members aged between 21 and 73 years who participated in a cross-sectional survey conducted in July 2020. We constructed the HLI by assigning one point to each healthy lifestyle factor: normal body mass index, sufficient physical activity, non-smoking status, non-to-moderate alcohol consumption, and sufficient sleep duration. The multivariate adjusted odds ratios for depressive symptoms were 1.00 (reference), 0.71, 0.66, and 0.56 for participants with HLI scores of 0 to 2, 3, 4, and 5, respectively. The present study suggests the role of healthy lifestyles in mental health among hospital staff working during the pandemic.